Study on heterogeneous traffic flow characteristics of a two-lane road / Heterogeninio transporto eismo srauto charakteristikos dviejų juostų kelyje / Характеристики гетерогенного потока движения на двухполосной дороге - Nitish Sharma; Shriniwas Shrikant Arkatkar; Ashoke Kumar Sarkar (Transport, 2011)
The paper presents traffic studies conducted by using a video capturing technique on the uninterrupted heterogeneous mix of vehicles plying on an undivided two-lane road facility. On the basis of the collected data, traffic characteristics pertaining to arrival, headway and speed distributions have been plotted considering suitable mathematical distributions to fit field observed values. The curves representing fundamental traffic flow relationships among three basic variables, namely speed, density and flow have also been established. Thus, a systematic attempt to enable the understanding of heterogeneous traffic flow parameters has been made through this exploratory study.